1.32 ± 0.11 Ma age for underwater remains constrain antiquity and longevity of the Dominican primate Antillothrix bernensis. Issue 88 (November 2015) - Rosenberger, Alfred L.; Pickering, Robyn; Green, Helen; Cooke, Siobhán B.; Tallman, Melissa; Morrow, Andrea; Rímoli, Renato
Abstract: Endemic New World monkeys are an important element of the extinct mammal faunas of the Caribbean's Greater Antilles. Here we report the first geochronometric evidence that the primate Antillothrix bernensis existed in the Dominican Republic during the Pleistocene, based on the uranium-series age of carbonate speleothem that encased a tibia when it was collected in a flooded cave. Three-dimensional geometric morphometrics of laser-scanned living and extinct samples provide evidence to support the hypothesis that this specimen and other Dominican primate tibial remains belong to that same species. U–Th dating of the host cave carbonate returns ages consistently at the 600 ka upper limit of the technique. However, U–Pb, capable of resolving ages of greater antiquity, is more robust in this context, returning a secure age of 1.32 ± 0.11 Ma, which is the oldest chronometric age recorded for a Hispaniolan mammal. While its origins and manner and time of arrival are obscure, the morphometric studies are consistent with phylogenetic analyses that place A. bernensis within the pitheciid clade of the platyrrhines. The species apparently endured for over 1 million years during the climatic perturbations of the Pleistocene, as a frugivorous climbing quadruped, one of two known primate species occupying the hazard prone island of Hispaniola.